2022
DOI: 10.1007/s00382-022-06388-w
|View full text |Cite
|
Sign up to set email alerts
|

Wind regime changes in the Euro-Atlantic region driven by Late-Holocene Grand Solar Minima

Abstract: This study has been funded by the Royal Society (ref: DH150185, RGF\EA\180100) and Horizon 2020 (MSCA EU project 705633 -SYNC). AAW is funded by the Natural Environmental Research Council (NE/L002485/1). We thank Professor Anson Mackay (University College London) for his support with diatom identification. We thank four anonymous reviewers for their constructive comments on the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
0
0
Order By: Relevance
“…Sjolte et al (2018) suggest a complex response to solar minima, which is not directly linked to NAO but rather to the Eastern Atlantic pattern with increased mid-Atlantic blocking and shifts to intensifying northerly winds resembling negative NAO conditions. Shifts in the Eastern Atlantic pattern during Grand Solar Minima are supported by Harding et al (2023) for the North Sea region.…”
Section: Nao Variability During the Past 3 Ka On An Interregional Scalementioning
confidence: 83%
See 1 more Smart Citation
“…Sjolte et al (2018) suggest a complex response to solar minima, which is not directly linked to NAO but rather to the Eastern Atlantic pattern with increased mid-Atlantic blocking and shifts to intensifying northerly winds resembling negative NAO conditions. Shifts in the Eastern Atlantic pattern during Grand Solar Minima are supported by Harding et al (2023) for the North Sea region.…”
Section: Nao Variability During the Past 3 Ka On An Interregional Scalementioning
confidence: 83%
“…These changes in solar activity triggered a rapid climate change and likely changes in atmospheric circulation patterns, which are linked to cooler and/or wetter and/or windier conditions (e.g. Engels et al, 2016;Martin-Puertas et al, 2012;Rach et al, 2017;van Geel et al, 2014;van Geel et al, 2000;Mellström et al, 2015;Harding et al, 2023;Martínez Cortizas et al, 2021). Some studies associate solar minima with shifts to a negative NAO (e.g.…”
Section: Nao Variability During the Past 3 Ka On An Interregional Scalementioning
confidence: 99%
“…Exploring the sensitivity of the geochemical record to temperature Previous investigations using the Diss Mere varves reveal a clear proxy response of the lake to climate variability. For example, a high-resolution diatom record from Diss Mere showed that the diatom assemblages responded to regional wind direction and strength during a Late Holocene climate oscillation 2800 years ago (Harding et al, 2022). In addition, the varve thickness record showed a good correlation to the simulated Atlantic Meridional Overturning Circulation (AMOC) and annual averaged surface temperature, resembling decadal-to millennial-scale climate variability in the North Atlantic region (Martin-Puertas et al, 2023).…”
Section: Productivity and Calcite Precipitation Over The Last Two Mil...mentioning
confidence: 98%
“…A wide range of techniques are used to interpret lake sediments and their associated forcing variables including: microfacies analysis (Brauer et al, 2008;Dräger et al, 2017); palaeoecological proxies such as pollen, diatoms and macrofossils (e.g. Harding et al, 2022;Müller et al, 2021); stable isotope analyses (e.g. Jonsson et al, 2010); and X-ray fluorescence (XRF) core scanning (e.g.…”
Section: Lake Sediments As Environmental Archivesmentioning
confidence: 99%
See 1 more Smart Citation